The Role of Implicit Attitudes in Populist Radical‐Right Support. Issue 1 (6th February 2017) - Bos, Linda; Sheets, Penelope; Boomgaarden, Hajo G.
Abstract : Previous research on the populist radical right (PRR) has focused exclusively on explicit measures in explaining support for these contested political players. In this study, we explore the role of implicit attitudes in predicting vote likelihood for a PRR party. We use an online survey ( n  = 773) among Dutch respondents in which we measured implicit attitudes towards the Dutch PRR Partij voor de Vrijheid (PVV) with a Single‐Target Implicit Association Test (ST‐IAT). The results show that the implicit measure predicts vote likelihood in general, as well as in ways beyond that accounted for by traditional explanations of PRR party support. Importantly, the results also show that the impact of implicit attitudes on intended vote choice is greater for less extreme voters; in other words, those voters less likely to say they would vote for the PVV are more heavily influenced at an implicit level, beyond their awareness. This suggests that implicit attitudes of the PRR party may be quite useful for explaining support among voters who would not normally self‐report it.